Planning in SMEs. - Goh, Teck Khoon. (2013)
The objective of our project is to study the incidence of formal strategic planning and outsider-based planning on the planning activities of the SmaU and Medium Enterprises (SMEs). We also research into the impact of these two planning activities on the effectiveness of the businesses. The research data was gathered through a series of interviews and questionnaires conducted with the SMEs of the Food and Beverages Industry.